Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Prestasi Kerja Karyawan Pada Institut Teknologi Dan Bisnis Nobel Indonesia - Andi Nabila Tenri Lala; M. Ikhwan Maulana Haeruddin; Abdi Akbar; Romansyah Sahabuddin; Uhud Darmawan Natsir (Jurnal Bisnis dan Kewirausahaan, 2023)
This study aims to (1) Know and analyse the effect of work discipline on employee performance at the Nobel Institute of Technology and Business Indonesia, (2) Know and analyse the effect of work environment on employee performance at the Nobel Institute of Technology and Business Indonesia, and (3) Know and analyse the effect of work discipline and work environment together on employee performance at the Nobel Institute of Technology and Business Indonesia. The population in this study were all employees, especially education personnel as many as 55 people. Sampling in this study was all members of the population, namely 55 people with quantitative research. The data collection technique was carried out by distributing questionnaires. The data analysis technique used is multiple linear regression analysis using Statistical Product Servive Solution (SPSS).The results showed that: 1) There is a positive and significant influence on work discipline on employee performance at the Nobel Institute of Technology and Business Indonesia, 2) There is a positive and significant influence on the work environment on employee performance at the Institute of Technology and Business Indonesia, and 3) There is a positive and significant effect of work discipline and work environment together on employee performance at the Nobel Institute of Technology and Business Indonesia.